1998
DOI: 10.1159/000030220
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Diabetes mellitus, Impotence and Veno-Occlusive Dysfunction in Peyronie’s Disease Patients

Abstract: Peyronie’s disease is an ill-defined condition that often leads to severe penile deformity and sometimes erectile dysfunction. Penile Doppler studies indicate veno-occlusive dysfunction as the principal cause of poor rigidity in Peyronie’s disease patients. Diabetes mellitus is also a known cause of impotence and its prevalence tended to be higher in patients with Peyronie’s disease. We evaluated 143 patients with Peyronie’s disease, also 92 impotent men (37 diabetic, 55 nondiabetic) as control group. Penile v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Schwarzer et al [5] found that the incidence of PD was three times greater in diabetics than non‐diabetics. Culha et al [16] also found a close relationship between diabetes mellitus and PD. On the contrary, Lindsay et al [8] reported that the incidence of diabetes mellitus was low among men with PD.…”
Section: Discussionmentioning
confidence: 94%
“…Schwarzer et al [5] found that the incidence of PD was three times greater in diabetics than non‐diabetics. Culha et al [16] also found a close relationship between diabetes mellitus and PD. On the contrary, Lindsay et al [8] reported that the incidence of diabetes mellitus was low among men with PD.…”
Section: Discussionmentioning
confidence: 94%
“…However, it should be noted that the study never examined whether PD (TA plaque) caused veno-occlusive dysfunction or ED. In another study that evaluated 143 PD patients, only 27 (19%) were found to have concomitant ED, and 22 (including 4 diabetics) of the 27 PD+ED patients were found to have veno-occlusive dysfunction [73]. So, on one hand, these two studies disagree sharply in the prevalence of ED among PD patients (80% versus 19%), but on the other, they do agree that veno-occlusive dysfunction is the principal cause of ED in PD patients.…”
Section: Peyronie's Disease-associated Edmentioning
confidence: 98%
“…PDE5 enzyme [19][20][21][22][23][24][25] converts cGMP into 5' AMP then lowering cGMP levels that are needed for the erection process. Medications such as sildefanil block the PDE5 enzyme then increasing and maintaining levels of cGMP necessary for the erection process.…”
Section: Erection Processmentioning
confidence: 99%